Given: 3x = 5 (x − 4) Prove: x = 10
========================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================================
Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10Given: 3x = 5 (x − 4) Prove: x = 10
![Given 3x 5 x 4 Prove x 10Given 3x 5 x 4 Prove x 10Given 3x 5 x 4 Prove x 10Given 3x 5 x 4 Prove x 10Given 3x 5 x 4 Prove x 10Given 3x 5 x 4 Prove x 10Given 3x 5 class=](https://us-static.z-dn.net/files/de2/33aef605464f8239f22284c31c456bdf.png)